2010
DOI: 10.1007/s00540-010-0886-5
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the κ-opioid receptor in nitrous oxide-induced analgesia in mice

Abstract: Nitrous oxide (N(2)O)-induced analgesia is thought to be mediated by endogenous opioids. We previously showed that the mu-opioid receptor is not required for the analgesic action of N(2)O in mice using a gene knockout approach. In this study, we examined the effect of kappa- (KOP)- or delta-opioid receptor (DOP)-selective antagonists on N(2)O-induced analgesia. The analgesic effect of N(2)O was evaluated using a writhing test. Male C57BL/6 mice aged 7-8 weeks were assigned to control, N(2)O, KOP agonist, and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…The antinociceptive action of N 2 O was also almost completely abolished in KOP-KO mice, consistent with our previous reports showing that the antinociceptive action of N 2 O was not influenced by genetic deletion of MOP in mice 5 and that a KOP-selective antagonist suppressed the antinociceptive effect of N 2 O. 6 These results together indicate that KOP performs an important function in the antinociceptive action of N 2 O. N 2 O activates the noradrenergic descending inhibitory pathway and GABAergic interneurons in the spinal cord in rat. 21 We have shown that inhalation of 70% N 2 O significantly increases the number of c-Fos-immunopositive cells in laminae III-IV in WT and MOP-KO mice, which reflects activation of GABAergic interneurons by the noradrenergic descending inhibitory pathway in the mouse spinal cord.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The antinociceptive action of N 2 O was also almost completely abolished in KOP-KO mice, consistent with our previous reports showing that the antinociceptive action of N 2 O was not influenced by genetic deletion of MOP in mice 5 and that a KOP-selective antagonist suppressed the antinociceptive effect of N 2 O. 6 These results together indicate that KOP performs an important function in the antinociceptive action of N 2 O. N 2 O activates the noradrenergic descending inhibitory pathway and GABAergic interneurons in the spinal cord in rat. 21 We have shown that inhalation of 70% N 2 O significantly increases the number of c-Fos-immunopositive cells in laminae III-IV in WT and MOP-KO mice, which reflects activation of GABAergic interneurons by the noradrenergic descending inhibitory pathway in the mouse spinal cord.…”
Section: Discussionsupporting
confidence: 92%
“…3 However, it is unclear which of the naloxone-sensitive opioid receptors, including the m-, k-, and d-opioid receptors (MOP, KOP, and DOP, respectively), 4 is the most important in the pharmacological action of N 2 O. Our previous report demonstrated that the antinociceptive effect of N 2 O is not influenced by genetic deletion of MOP 5 and is significantly reduced by a KOP-selective antagonist, but unaffected by a DOP-selective antagonist, 6 suggesting that KOP is important in the antinociceptive action of N 2 O.…”
mentioning
confidence: 99%
“…The poor substitution produced by m-opioid agonist morphine is consistent with data showing that the opioid antagonist naloxone does not attenuate the subjective effects of 30% N 2 O in humans (Zacny et al, 1994(Zacny et al, , 1999. Likewise, the failure of the d-opioid agonist SNC-80 to substitute for N 2 O is consistent with reports that the d-opioid receptor agonist naltrindole does not attenuate N 2 O analgesia (Koyama and Fukuda, 2010). Our data showing that the selective k-opioid agonist U50-488H does not substitute for N 2 O is, however, in conflict with a previous study in which N 2 O generalized to the purported k-opioid agonist ethylketocyclazocine in guinea pigs trained to discriminate ethylketocyclazocine from vehicle (Hynes and Hymson, 1984).…”
Section: Discussionsupporting
confidence: 87%
“…The k-opioid antagonist nor-binaltorphimine but not the d-opioid antagonist naltrindole attenuates N 2 O analgesia (Koyama and Fukuda, 2010). A mixed agonist/antagonist at m-opioid receptors, b-chlornaltrexamine reverses N 2 O antinociceptive responses (Emmanouil et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrous oxide has effects on the endogenous opioid system that could contribute to analgesia and perhaps, to psychotropic effects [112][113][114][115]. Some evidence indicates that nitrous oxide exerts preferential effects on kappa-type opiate receptors over mu-type receptors [116,117]. Modulation of the opiate system may be important for antidepressant effects given recent evidence suggesting that an opiate receptor antagonist dampens the antidepressant effects of ketamine [80].…”
Section: Putative Mechanisms Of Nitrous Oxide Antidepressant Effectsmentioning
confidence: 99%